Strengthening Pemahaman Mahasiswa terhadap Pondok Pesantren sebagai Mata Kuliah di Universitas Sains Al-Qur’an Wonosobo - Robingun Suyud El Syam (Journal Innovation In Education, 2023)
This research is an effort to examine the strengthening of students' understanding of Islamic boarding schools as a subject at the Wonosobo Al-Qur'an Science University. This research was conducted using a qualitative descriptive approach where data was analyzed using interviews. Research findings show that careful observation of students' understanding of Islamic boarding school studies courses increasingly shows how these courses have contributed to increasing understanding among students who have taken these courses. The right support and reference system helps students have a comprehensive understanding of Islamic boarding schools. Research implications: This understanding is in accordance with the current condition of Islamic boarding schools which are making changes according to the times, without abandoning their roots. This study recommends making Islamic boarding school studies a course in universities so that wrong understanding can be avoided.